Automatic identification of areas with low‐voltage fragmented electrograms for the detection of the critical isthmus of atypical atrial flutters. - Franco, Eduardo; Lozano Granero, Cristina; Cortez‐Dias, Nuno; Nakar, Elad; Segev, Meytal; Matía, Roberto; Hernández‐Madrid, Antonio; Zamorano, José Luis; Moreno, Javier (Journal of Cardiovascular Electrophysiology, 2023)
Introduction: Critical isthmuses of atypical atrial flutters (AAFLs) are usually located at slow conduction areas that exhibit fractionated electrograms. We tested a novel software, intended for integration with a commercially available navigation system, that automatically detects fractionated electrograms, to identify the critical isthmus in patients with AAFL ablation. Methods and Results: All available patients were analyzed; 27 patients with 33 AAFLs were included. The PentaRay NAV catheter (Biosense Webster) was used for mapping. The novel software was retrospectively applied; fractionated points with duration ≥80 ms and bipolar voltage between 0.05 and 0.5 mV were highlighted on the surface of maps. In 10 randomly chosen AAFLs, an expert electrophysiologist evaluated the positive predictive value of the algorithm to detect true fractionation: 74.4%. We tested the capacity of the software to identify areas of fractionation (defined as clusters of ≥3 adjacent points with fractionation) at the critical isthmus of the AAFLs (defined using conventional mapping criteria). An area of fractionation was identified at the critical isthmus in 30 cases (91%). Globally, 144 areas of fractionation (median number per AAFL 4 [3–6]) were identified. Duration of the fractionation or the surface of the areas was not different between areas at critical isthmuses and the rest. Setting the fractionation score filter of the software in nine provided best performance. Conclusions: The novel software detected areas of fractionation at the critical isthmus in most AAFLs, which may help identify the critical isthmus in clinical practice.